1978
DOI: 10.1111/j.1365-2044.1978.tb08280.x
|View full text |Cite
|
Sign up to set email alerts
|

The cost of anaesthetic drugs and equipment

Abstract: A review of the literature and an up-to-date estimate shows that despite inflation, the cost of anaesthesia has stayed fairly constant over the last 17 years. A questionnaire completed by a small number of junior anaesthetists showed only a fair, and at times widly inaccurate, knowledge of the cost of anaesthetic drug and equipment. An up-to-date price list of commonly used drugs and equipment is included, along with the cost of some common anaesthetic techniques.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

1990
1990
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…Even though significant errors were observed in the cost estimations, this study indicates that knowledge of prices of anaesthesia has improved when compared to the relatively few studies that have addressed the issue of cost awareness previously. In 1978 Simpson (6) questioned five junior anaesthetists about their knowledge of costs of five drugs. In comparison with our junior anaesthetists they were less accurate.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Even though significant errors were observed in the cost estimations, this study indicates that knowledge of prices of anaesthesia has improved when compared to the relatively few studies that have addressed the issue of cost awareness previously. In 1978 Simpson (6) questioned five junior anaesthetists about their knowledge of costs of five drugs. In comparison with our junior anaesthetists they were less accurate.…”
Section: Discussionmentioning
confidence: 99%
“…In the few studies on cost consciousness amongst anaesthetic staff the number of staff members questioned has been limited, but the results indicate that cost consciousness amongst anaesthetic staff is limited (3)(4)(5)(6).…”
mentioning
confidence: 99%
“…In previous studies it has been reported that there is inadequate awareness as regards to such costs. 5 - 9 In a study using a 25-item questionnaire about drugs used in anesthesia practice, Javasuriya et al showed that there was inadequate awareness regarding costs and that this was not affected by experience. 9 The authors also noted that all estimations of prices were below the actual prices.…”
Section: Discussionmentioning
confidence: 99%